P264 ROLE OF BLOOD GAS ANALYSIS AND D–DIMER IN RAISING THE SUSPICION OF MASSIVE PULMONARY EMBOLISM IN GERIATRIC PEOPLE: THE EMERGENCY ROOM AS A WINDOW INTO REAL LIFE. (18th May 2022) - Savioli, G; Ceresa, I; Mugellini, A; Martignoni, A; Fumoso, F; Lapia, F; Preda, L; Manzoni, F; Brattoli, M; Maggioni, P; Novelli, V; Muzzi, A; et al.
Abstract: Premise: Massive pulmonary embolism is burdened with high mortality. Raising suspicion and recognizing this condition early allows to avoid delays in the diagnostic and therapeutic process. Purpose: Assess which parameters of blood gas analysis, in the real life of an Emergency Department, correlate with the presence of massive pulmonary embolism to see which ones can help to suspect it early. Methods: single–center retrospective observational study, on all geriatric patients (> 75 y) who entered our ED, where they were diagnosed with acute PE. Enrollment began in 2016 and ended in 2019. We collected data from medical history, physical examination, laboratory tests, imaging; we calculated the characteristic scores from the diagnostic / therapeutic algorithm, both for the risk of PE (Wells, Geneva and YEARS), and for the presentation of the risk of mortality at 30 days (sPESI). We looked at all the blood gas analyzes performed at the emergency room access. We then had all chest CTs retested by an experienced radiologist. Results: We enrolled 247 patients, with a mean age of 83 years with prevalence of female prevalence (F = 63%). Of these, 85 (34.4%) have massive pulmonary embolism. Lactates do not correlate with the presence of massive pulmonary embolism (p > 0.05). The pCO2 values correlate inversely with the presence of massive pulmonary embolism with excellent statistical strength (p < 0.0001). The reduction in pO2 values also correlates with the presence of massive pulmonary embolism, with good statistical strength (p < 0.005). The increase in pH values also correlates with the presence of massive pulmonary embolism, albeit with a lower statistical strength (p < 0.05). The D–Dimer shows a strong association with massive pulmonary embolism values (p < 0.0001). Conclusions: The study suggests that the reduction of pCO2 values, with an increase in pH and D–Dimer show a strong correlation with the condition of massive pulmonary embolism. Similarly, the pO2 can play a role in the identification of this condition, while no role would seem to have the alteration of lactates. Taking into consideration these parameters, which are quickly available and easily performed in the various Italian situations, can help to raise the suspicion of massive pulmonary embolism early and direct the patient more quickly towards the therapeutic diagnostic process.